PENGARUH KOMITMEN ORGANISASI, SISTEM PENGENDALIAN INTERN PEMERINTAH, DAN PERAN PENGELOLA KEUANGAN DAERAH TERHADAP KINERJA MANAJERIAL SATUAN KERJA PERANGKAT DAERAH KOTA PEKANBARU - Noval Hadi Praja; Andreas -; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of organizational commitment, the Government's internal control system, and the role of the Financial Manager Of The Managerial performance of SKPD’s Pekanbaru City. This study was conducted at SKPD of Pekanbaru City. The population in this study were employer who worked in the SKPD Kampar Regency (26 government agencies). The sampling method used in this study is purposive sampling method. The respondent in this study is the head officer of SKPD, the secretary of SKPD and the head of financial SKPD. The sample used in this study were 78 respondents. The hypotheses then tested is multiple linear regression analysis by using SPSS version 20. The result of this study indicated that the influence of organizational commitment, the system of internal control of the Government, and the role of the Financial Manager Of The Managerial performance has significantly effect on effectiveness of the Performance Managerial. The magnitude of the effect (R2) The organizational commitment, the system of internal control of the Government, and the role of the Financial Manager Of The Managerial performance area was 28%. While the remaining 72% is influenced by other independent variabel that are not observed in this study.Keywords: Organizational commitment, system internal control, Financial Manager, and Performance.